Problematika Pesta Pernikahan Antara Kakak Beradik di Tahun yang Sama Pada Masyarakat Desa Teluk Bakung Tanjung Pura Menurut ‘Urf dalam Hukum Islam - Sri Herianda (Peduli Riset dan Pengabdian Masyarakat, 2024)
Marriage is sacred for all humans. However, the prohibition of marriage is certainly an obstacle to this sacredness. In the tradition of the Malay and Javanese communities in Teluk Bakung Village, Tanjung Pura District, there is a tradition that prohibits the marriage of siblings in the same year. This tradition has been passed down from ancestors, if violated, the community believes that the household will not be able to live in harmony and peace so that it is difficult to realize a sakinah, mawaddah, and rahmah household. However, this tradition is contrary to Islamic law where the prohibition of marriage can only arise from the consequences of lineage, different religions, previous marriage relationships, the consequences of divorce, and during the iddah period. This study discusses how the prohibition of marriage between two siblings in the same year for the Javanese and Malay tribes in Teluk Bakung Village and what factors cause the prohibition of marriage between siblings in the same year. This type of research uses qualitative research. The data used are primary data and secondary data obtained through interviews. The data is then processed and analyzed using a qualitative approach. The results of the study show that the prohibition of marriage between siblings in the same year is caused by several things. First, the belief that is passed down from ancestors from generation to generation. Second, there is a belief in the bad impact or disaster if the community continues to carry out the prohibition, as in several examples of cases that already exist